2018
DOI: 10.1177/1471301218805329
|View full text |Cite
|
Sign up to set email alerts
|

Communication Empowerment Framework: An integrative framework to support effective communication and interaction between carers and people living with dementia

Abstract: To demonstrate the power of integrating three theoretical perspectives (Mentalization Theory, Perceptual Control Theory and the Communicative Impact model), which jointly illuminate the communication challenges and opportunities faced by family carers of people with dementia. To point the way to how this framework informs the design and delivery of carer communication and interaction training. Method: Conceptual synthesis based on a narrative review of relevant literature, supported by examples of family carer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 74 publications
0
40
0
Order By: Relevance
“…However, in a recent systematic review of the field, Morris et al (2017) found that while many such interventions are successful in terms of improving carers' knowledge of communication skills and strategies, only a minority actually have an impact on their levels of wellbeing. It has been suggested that one reason for this is that many interventions lack, or fail to adequately integrate, an appropriate theoretical model (Morris et al, 2018), and that this shortcoming can prevent an understanding of the mechanisms through which beneficial effects are realised (Elvish et al, 2013;Popay et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent systematic review of the field, Morris et al (2017) found that while many such interventions are successful in terms of improving carers' knowledge of communication skills and strategies, only a minority actually have an impact on their levels of wellbeing. It has been suggested that one reason for this is that many interventions lack, or fail to adequately integrate, an appropriate theoretical model (Morris et al, 2018), and that this shortcoming can prevent an understanding of the mechanisms through which beneficial effects are realised (Elvish et al, 2013;Popay et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Communication Empowerment Framework draws together three theoretical accounts of how humans negotiate their world and maintain well-being: (1) Mentalization Theory relates to our perceptions of ourselves and others; (2) Perceptual Control Theory explains how conflicting internal and interpersonal goals can reduce control and impact on our relationships and (3) The Communicative Impact Model accounts for the complex and contradictory challenges of dementia care in terms of the intricate parameters of successful communication. These three models and their integration are described in detail in Morris et al (2018a). The synthesis of these three accounts informs targeted strategies and interactive exercises that facilitate carers to consider the goals and emotions of those they are caring for, alongside their own goals and emotions, and to use this to maximize good communication.…”
mentioning
confidence: 99%
“…Family carers provide intense practical support, whilst coming to terms with changes in their relationship ( Morris et al, 2018a ). Research indicates that about 40% of family carers 1 of people with dementia have clinically significant depression or anxiety ( Cooper et al, 2007 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The goal is to foster the ability of carers to reflect upon their communicative interactions, so that they can support their relatives with dementia in less reactive, more responsive ways. In order to achieve this goal, it is essential for carers to pay attention to the pragmatics of communication, as well as an experiential understanding of what may be happening for the person with dementia (Wray, 2016;Morris et al, 2018). Attending to the pragmatics of communication such as the worries carers may have about saying the right thing, provides a safe entry point for carers to reflect upon their experiences.…”
mentioning
confidence: 99%